Peningkatan Aktivitas Dan Hasil Belajar Siswa Melalui Pendekatan Inkuiri Pada Pembelajaran IPA Kelas V Sekolah Dasar - Ningsih, Dahlia (Universitas Sebelas Maret, 2020)
At the learning of students' activities on science learners is low and tend to use lecture methods. The lack and lack of student activity in the study of science can affect the students' learning. The purpose of this study is to find out the positive correlation between student activity and the results of studying earth class IV SDN 07 TUIK 2017/2018. Research is done in 2 cycles and each cycle consists of two meetings. The study instumen consists of an objective text, an essay, and an observation sheet of student activity and the teacher aspect. Research shows an increase in students' activities of the 1 meeting of 1 59.31% and the second meeting was increased by 68.13%. The second cycle of meeting I was 85,78% and the second meeting had an increase of 90,68%. The sharp results of each student study cycle I 69.97%, and on cycle ii is 80.18%. Based on analysis and discussion of research results it suggests that the positive correlation between learning activities and the study of science students iv SDN 07 Tuik year 2017/2018.